2022
DOI: 10.1021/acsomega.2c04564
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Methacrylate-Based Copolymers: Recent Developments in the Areas of Transparent and Stretchable Active Matrices

Abstract: The recent advancements of poly­(methyl methacrylate) (PMMA) as a transparent flexible polymer material have been utilized in numerous areas of engineering and materials science. PMMA-based copolymers demonstrate outstanding mechanical and optical properties owing to high transparency, lightweight nature, high impact resistance, and stress relaxation across glass transition temperature. These copolymers have unique characteristics of retaining optical and microstructural integrities during successive bending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 120 publications
0
15
0
1
Order By: Relevance
“…Reversible addition-fragmentation chain transfer (RAFT) polymerization technique was utilized for all syntheses owing to its versatility, ability to synthesize polymers with complex architectures, and narrow molar mass distributions. [31][32][33] First, a kinetic study was conducted with DMAEMA, LAMA, and nBMA as monomers to establish uniform reaction conditions for all polymerizations. The kinetics were performed over a 21 h period at 70 °C using 4-Cyano-4-[[(ethylthio)thioxomethyl]thio]pentanoic acid (CPAETC) as the chain transfer agent and 4,4′-azobis(4cyanovaleric acid) (ACVA) as initiator (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Reversible addition-fragmentation chain transfer (RAFT) polymerization technique was utilized for all syntheses owing to its versatility, ability to synthesize polymers with complex architectures, and narrow molar mass distributions. [31][32][33] First, a kinetic study was conducted with DMAEMA, LAMA, and nBMA as monomers to establish uniform reaction conditions for all polymerizations. The kinetics were performed over a 21 h period at 70 °C using 4-Cyano-4-[[(ethylthio)thioxomethyl]thio]pentanoic acid (CPAETC) as the chain transfer agent and 4,4′-azobis(4cyanovaleric acid) (ACVA) as initiator (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Hawker et al demonstrated that the use of PDMS-block-PMMA helps to create domain periods as small as 12.1 nm, which is one of the smallest highly ordered nanoscale patterns (Figure 4). This opens up the possibility of creating nanoscale processors, transistors, and devices with high resolution by sub-10 nm lithography [63,64]. Optical transparency is desirable for polymer material in order for it to be used in optoelectronics.…”
Section: Transparency Morphology and Adhesionmentioning
confidence: 99%
“…The transparency of the material was adjusted by changing the molar ratio MOI (x) in SigUMAx. Despite the improved optical properties, PDMS-block-PMMA copolymers have not been widely applied in the field of optoelectronics, because their preparation involves multiple stages of synthesis [62,63,65].…”
Section: Transparency Morphology and Adhesionmentioning
confidence: 99%
“…Poly­(methyl methacrylate) (PMMA) has the advantages of high transparency, high mechanical strength, lightweight, easy processing, good dielectric properties, and insulation, and has been widely used in various fields such as architecture, aviation, medicine, and the chemical industry. It is also used in museum artifact preservation and exhibition, allowing archeologists and other researchers to directly observe artifacts. Due to the characteristics of this organic polymer material, long-term exposure to sunlight and air can result in a certain degree of aging, which manifests as molecular chain degradation and molecular weight reduction at the microscopic level, and a decrease in optical properties such as light transmittance, as well as reduced toughness, tensile strength, and fatigue strength at the macroscopic level . Therefore, it is necessary to regularly check its aging degree and replace it according to a cycle to prevent the reduction of light transmittance and yellowing caused by PMMA aging from affecting the display effect of artifacts or even causing them to crack and damage.…”
Section: Introductionmentioning
confidence: 99%